Associations among the Degree of Hip Adductor Spasticity, the Level of Gross Motor Function Classification System (GMFCS) and the Migration Percentage in Children with Cerebral Palsy - Lindrawati Tjuatja; Aryadi Kurniawan; Damayanti Sekarsari; Hamzah Shatri; Luh Karunia Wahyuni (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Objectives : This study was aimed at detecting the occurrence of hip dislocation in children with cerebral palsy (CP) by seeking the association among the degree of hip adductor spasticity, level of Gross MotorFunction Classification System (GMFCS) and Migration Percentage (MP).Methods : It was a cross sectional study with inclusion criterias were children with cerebral palsy, both male and female aged 2-10 years old, and parent’s approval by signing informed consent. Exclusion criterias werecomorbidities of other neuromotor impairments, such as spina bifida; other neuromuscular or musculoskeletal diseases, etc; uncooperative; and presenting severe diseases at the day of assessment. Measurement methodsincluded the Modified Tardieu Scale (MTS) R2, R1 and R2-R1 components to measure hip adductor spasticity; Gross Motor Function Classification System (GMFCS) protocol to assess gross motor ability; andAnterior-Posterior (AP) pelvic plain radiograph to calculate the Migration Percentage (MP) value.Results : At the initial phase, 31 children were included, however only 57 legs were analyzed for hip adductor spasticity and MP. There were no correlation between the degree of hip adductor spasticity and MPboth the R2 with MP (r = -0.060; p = 0.658), and R1 with MP (r = -0.136; p = 0.314). Moreover, there was insignificant difference between level of GMFCS and MP (p = 0.831).Conclusion : This study indicates nill correlation between the degree of hip adductor spasticity and the MP, and insignificant difference between the level of GMFCS and MP to detect the occurence of hip dislocationin children with cerebral palsy.Keywords : Modified Tardieu Scale, R2, R1, level of GMFCS, AP pelvic plain radiograph, MP value.